Penerapan Manajemen Kurikulum Merdeka Belajar untuk Meningkatkan Kualitas Pendidikan - Fatma Sari; Iswantir M; Susanda Febriani (Journal of Management and Creative Business, 2024)
A good education will produce a generation or human resources that excel in various aspects of life by freeing students from ignorance and inability. To address education issues during and after the pandemic, the government launched the independent curriculum programme. While the essence of the previous curriculum is maintained, this innovation adds variations that support the strengthening of students' characters, making it a new step from the government. This research on the independent curriculum was conducted using the library research method. This method involves reviewing various relevant literature and writings, such as books, journals, articles, theses, and sources from the internet. The results show that the independent curriculum requires less administration compared to the previous curriculum. The preparation of a simpler Allocation of Learning Time (ATP) but still in accordance with the learning objectives allows teachers to focus more and improve the effectiveness of classroom teaching. In general, student learning activities in the independent curriculum are not much different from the previous curriculum. The main difference lies in the simplification of teaching materials by teachers. In addition, in an effort to shape student character, the time allocation in the independent curriculum is clearer and the actions taken are more tangible. This is achieved through the Pancasila Student Profile Strengthening Project (P5), which aims to instil Pancasila character values in students' daily lives.